Early molecular response in chronic myeloid leukemia and halving time: Latest evidences. (September 2016) - Breccia, Massimo; Molica, Matteo; Colafigli, Gioia; Massaro, Fulvio; Alimena, Giuliana
Highlights: Early molecular response in CML corresponds to a ratio BCR-ABL1/ABL <10% IS at 3 months. Achievement of EMR with imatinib indicated positive long-term outcome. EMR maintain its validity with second generation TKIs as frontline treatment. Halving time indicated the kinetics of ratio BCR-ABL1/ABL decline. Abstract: Achieving a BCR-ABL/ABL ratio <10% at 3 months has become an important goal of treatment for chronic myeloid leukemia (CML) patients treated with tyrosine kinase inhibitors. Several evidences showed that this early molecular response (EMR) is associated with positive long-term outcome in terms of overall survival and progression-free survival, but a consensus has not been reached when this goal is not achieved. European LeukemiaNet recommendations defined patients as treatment failure only after the 6- month time point. Not all patients that lack EMR have similar outcome and it became important to identify patients before this time point of 3 months. Several groups introduced the concept of "halving time" or "velocity of ratio reduction" that could anticipate the possibility to recognize patients deserving a switch to another treatment. Aim of this review is to summarize all evidences reported on the significance of EMR and how this evaluation changed our perspectives and modified our therapeutic strategies.